"Church, Family, Hard Work, and Dutch Clean": Jeugdherinneringen, godsdienst en etniciteit van Nederlandse immigranten in Amerika - Elster, Peter (Religie & Samenleving, 2009)
This article pictures the youth memories of older Dutch-Americans who grew up in the “Dutch enclave” of Holland, Michigan (USA). This area is heavily populated by Dutch immigrants sharing traditional Calvinist religious values, norms, and beliefs. Findings are based on oral interviews among a sample of older respondents from the area (mean age is 81 yrs.). The study combines a generational approach with an oral history methodology. Results indicate that respondents cherish their formative years, their Calvinist Dutch-American upbringing, and feel that their socialization in strict values, norms and beliefs had lasting effects on their personal life course and life style. Of the two basic ingredients of their cultural identity – Dutch descent and Reformed religion – faith is far more important than ethnicity. Studying narrative youth memories of members of the oldest generation of (Dutch) Americans is a fascinating topic for social scientists as this generation is about to be replaced and their stories will soon be forgotten.